Structural behaviour of circular concrete filled steel tube column fill with selfcompacting concrete incorporating coal bottom ash as fine aggregate replacement - Zainal Abidin, Norul Ernida (2019)
Lack of compaction may affect the interaction between the steel tube and the concrete, hence influence the behaviour of CFST column. Employing selfcompacting concrete (SCC) in CFST column as an infill concrete remove the necessity for compaction. However, higher volume of fine aggregate required in SCC makes SCC less preferable. The objective of this research was to investigate the behaviour of circular CFST column filled with SCC incorporating coal bottom ash (CBA) as fine aggregate replacement. In this research work, sand was replaced with CBA at 10%, 15%, 20%, 25%, and 30% of replacement levels. Tests for compressive strength, split tensile strength, flexural strength, and water absorption were performed on specimens at 7 and 28 days curing age. The testing results show that 15% of CBA was the optimum percentage suitable used in SCC. In studying the behaviour of CFST columns, 18 CFST column specimens were tested to fail under the axial compression loading. From the experimental results, it can be concluded that the utilisation of SCC with CBA in the CFST column able to improve the behaviour of CFST column. From compression testing results, the strength of CFST column filled with SCC with CBA increased about 45-50%. The experimental results were also compared with the design standard of Eurocode 4 (EC4). From the comparison, the EC4 conservatively predicts the strength of the column specimens. For instance, EC4 conservatively predicted the column strength in series I by about 21-31%. The finite element analysis (FEA) was conducted on the long column to verify the experimental results and from the FEA result, the predicted value for specimens with 140 mm diameter is 0.005% closer to the experimental results. These discoveries are significant as they showed that the utilization of CBA in SCC as an infill in CFST column able to provide the same strength as CFST with normal SCC. Besides, the use of CBA as partially replacement to the sand will help in more sustainable SCC production by lowering energy and raw material consumption.